The lineman's and cableman's field manual - Shoemaker, Thomas M. 1921- (McGraw-Hill, 2000)
One-stop portable reference for linemen and cablemen. Take all the key information you need to every jobsite in one easy-to use reference! Lineman's and Cableman's Field Manual, by Thomas M. Shoemaker and James E. Mack, packs the latest NEC« and OSHA standards and safety rules pertaining to electrical line maintenance and construction.